Ad libitum feeding alters mRNA abundance in the ovarian cortex of broiler breeder hens. Issue 2 (20th June 2022) - Anthony, Kate; Garner, Tyler Bruce; Ramachandran, Ramesh; Diaz, Francisco Javier
Abstract : Ad libitum: feeding in broiler breeder (BB) hens causes reduced egg production, lower fertility, and improper eggshell deposition. Restricted feeding (RF) is the only effective intervention available to normalize ovarian function and improve reproductive efficiency. This study aimed to assess the transcriptional changes in ovarian cortex of BB hens with free access to feed compared to those on a RF diet. RNA was isolated from the ovarian cortex of Cobb 500 pullets raised to 10 and 16 weeks of age on either a full-feeding (FF) or RF diet. Microarray analysis identified 386 differentially expressed genes between the two feeding groups at 16 weeks of age. Gene ontology enrichment identified overrepresentation of Neuroactive ligand–receptor interaction pathways, Cell adhesion molecules, Steroid hormone biosynthesis, and various KEGG pathways. From these groups, 46 genes were selected for follow-up validation by quantitative PCR. The findings show that 33 of the 46 genes had significantly different abundance by age and/or feeding level. Most of these genes were repressed in RF hens and belonged to the steroid biosynthesis and neuropeptide signaling groups. The VIPR2 receptor was higher in the FF group leading us to hypothesize that vasoactive intestinal peptide (VIP) is an important regulator of small cortical follicles. Culture of hen cortical follicles with VIP increased Star, an indication of increased steroidogenic activity, although did not elevate Cyp11a1 . These results offer insights and suggest the possible mechanisms and pathways responsible for the increases in cortical follicle growth associated with excess feed intake in BB hens. Lay summary: Giving breeder hens unrestricted access to feed can lead to problems with their ovaries, including excessive growth of the ovary and reduced fertility. Giving a limited amount of feed is the only effective way to reduce this growth of the ovaries and improve fertility. This study aimed to assess the changes in the molecules that make proteins in the body in hens fed unrestricted and restricted diets. In the hens fed a limited amount of feed, there were more of one type of molecules, while there were more of another type in the ovaries of hens with unrestricted access to feed. These results show that how much a hen eats can alter the number of these molecules in the ovary and this could help us understand why their ovaries grow excessively and why their eggs are less fertile.